2013
DOI: 10.3892/etm.2013.1360
|View full text |Cite
|
Sign up to set email alerts
|

Expression of toll-like receptor 4 in maternal monocytes of patients with gestational diabetes mellitus

Abstract: Toll-like receptors (TLRs) are pattern recognition receptors and play an important role in innate immune responses and the occurrence of inflammatory disease. TLR4 is a member of the TLR family and its activation is capable of inducing inflammatory responses, reflecting a relationship between the innate and adaptive immune systems. However, whether TLR4 is expressed in patients with gestational diabetes mellitus (GDM) has not been elucidated. The aim of the present study was to investigate whether TLR4 is expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…There is evidence regarding a role for the TLR4 signaling pathway and the innate immune response in the development of cardiovascular pathologies with an inflammatory component such as atherosclerosis [14], diabetes [26][28] and pre-eclampsia [29], [30]. Hypertension has also been considered as a low-grade inflammatory disease, and growing evidence shows that the immune system is involved in the pathophysiology of hypertension [2][4].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence regarding a role for the TLR4 signaling pathway and the innate immune response in the development of cardiovascular pathologies with an inflammatory component such as atherosclerosis [14], diabetes [26][28] and pre-eclampsia [29], [30]. Hypertension has also been considered as a low-grade inflammatory disease, and growing evidence shows that the immune system is involved in the pathophysiology of hypertension [2][4].…”
Section: Discussionmentioning
confidence: 99%
“…Further, elevated PBMC, TLR2 and TLR4 mRNA expression was evident in GDM in the second trimester; however, 4 weeks later, the difference was not significant, probably as a result of an increase in TLR expressions in the healthy pregnant women (Kuzmicki et al 2013). On the other hand, another study reported that TLR4 mRNA expression was significantly higher in maternal monocytes of patients with GDM obtained after 37 weeks gestation (Xie et al 2014). Additionally, there was a positive correlation between the TLR4 mRNA expression level in peripheral blood monocytes and serum TNF-α levels (Xie et al 2014).…”
Section: Toll-like Receptors (Tlrs)mentioning
confidence: 90%
“…On the other hand, another study reported that TLR4 mRNA expression was significantly higher in maternal monocytes of patients with GDM obtained after 37 weeks gestation (Xie et al 2014). Additionally, there was a positive correlation between the TLR4 mRNA expression level in peripheral blood monocytes and serum TNF-α levels (Xie et al 2014).…”
Section: Toll-like Receptors (Tlrs)mentioning
confidence: 98%
“…TNFα is perhaps the most extensively studied cytokine in this context, with most studies finding a positive association with GDM 9396, and for reviews see 86,87 . While some others have reported no changes in TNFα with GDM 91,97,98 , overall the literature suggests a fairly reliable association of elevations in TNFα with GDM 87 . CRP elevation in GDM is a consistent finding also 98102 .…”
Section: Inflammatory Mediators: Parallels Between Gestational Diabetmentioning
confidence: 85%
“…These findings indicate a deficiency in the processes that downregulate immune activation in order to support maternal-fetal tolerance. Conversely however, the Toll-like receptors TLR2 and TLR4, which promote activation of inflammatory mediators, are increased in peripheral blood mononuclear cells of women with GDM 91,92 .…”
Section: Inflammatory Mediators: Parallels Between Gestational Diabetmentioning
confidence: 95%